Growth performance, jejunal morphology, disaccharidase activities, and sugar transporter gene expression in Langde geese as affected by the in ovo injection of maltose plus sucrose - Li, Desheng; Dang, De Xin; Xu, Han; Zhou, Haizhu; Lou, Yujie; Liu, Xiao; Cui, Yan (Frontiers in Veterinary Science, 2023)
Vigorous metabolic activities of the embryo increase the risk of insufficient energy supply during the incubation. The shortage of energy in this critical period will lead to embryo death. Technique of in ovo injection allows for injecting energy substance into embryo to avoid this risk. This study investigated the effects of maltose and sucrose (MS) in ovo injection on post-hatching growth performance, jejunal morphology, jejunal disaccharidase activities, and sugar transporter gene expression in Langde geese. A total of 300 fertilized eggs (115.75 ± 1.25 g) obtained from Langde geese at 3 years old were used in this experiment. Eggs were randomly assigned into two groups, difference between the two groups was whether 7.5g/L NaCl dissolved with 25g/L maltose and 25g/L sucrose (MS) was injected into the amnion on embryonic day 24 or not. There were 6 replicates per group and 25 eggs per replicate. Goslings were raised till day 28 of age. Results showed that in ovo injection of MS increased final body weight, average daily gain, and feed efficiency. Additionally, the improvement of post-hatching jejunal morphology, disaccharidase activities, and sugar transporter gene expression in the early-stage were observed by MS injection. Therefore, we considered that MS in ovo injection had positive effects on nutrient absorption capacity of goslings and thus contributed to improve growth performance.